Comparison of Eye Movement Desensitization Reprocessing and Cognitive Behavioral Therapy as Adjunctive Treatments for Recurrent Depression: The European Depression EMDR Network (EDEN) Randomized Controlled Trial - Ostacoli, Luca; Carletto, Sara; Cavallo, Marco; Baldomir-Gago, Paula; Di Lorenzo, Giorgio; Fernandez, Isabel; Hase, Michael; Justo-Alonso, Ania; Lehnung, Maria; Migliaretti, Giuseppe; Oliva, Francesco; Pagani, Marco; et al. (Frontiers in Psychology, 2018)
Background: Treatment of recurrent depressive disorders is currently only moderately successful. Increasing evidence suggests a significant relationship between adverse childhood experiences and recurrent depressive disorders, suggesting that trauma-based interventions could be useful for these patients. Objectives: To investigate the efficacy of EMDR in addition to antidepressant medication in treating recurrent depression. Design: A non-inferiority, single-blind, randomized clinical controlled trial comparing EMDR or CBT as adjunctive treatments to antidepressant medication. Randomization was carried out by a central computer system. Allocation was carried out by a study coordinator in each center. Setting: Two psychiatric services, one in Italy and one in Spain. Participants: Eighty-two patients were randomized with a 1:1 ratio to the EMDR group (n=40) or CBT group (n=42). Sixty-six patients, 31 in the EMDR group and 35 in the CBT group, were included in the completers analysis. Intervention: 15±3 individual sessions of EMDR or CBT, both in addition to antidepressant medication. Participants were followed up at six-months. Main outcome measure: Rate of depressive symptoms remission in both groups, as measured by a BDI-II score <13. Results: Sixty-six patients were analyzed as completers (31 EMDR vs. 35 CBT). No significant difference between the two groups was found either at the end of the interventions (71% EMDR vs. 48.7% CBT) or at the six-month follow-up (54.8% EMDR vs. 42.9% CBT). A RM-ANOVA on BDI-II scores showed similar reductions over time in both groups (F(6, 59) = 22.501, p< .001) and a significant interaction effect between time and group (F(6, 59) = 3.357, p= .006), with lower BDI-II scores in the EMDR group at T1 (mean difference= -7.309 (95% CI [- 12.811, -1.806]), p= .010). The RM-ANOVA on secondary outcome measures showed similar improvement over time in both groups (F(14, 51) = 8.202, p< .001), with no significant differences between groups (F(614, 51) = 0.642, p= .817). Conclusion: Although these results can be considered preliminary only, this study suggests that EMDR could be a viable and effective treatment for reducing depressive symptoms and improving the quality of life of patients with recurrent depression. Trial registration: ISRCTN09958202. Funding: EMDR Research Foundation.